Prenatal diagnosis and molecular cytogenetic characterization of concomitant familial small supernumerary marker chromosome derived from chromosome 4q (4q11.1-q13.2) and 5q13.2 microdeletion with no apparent phenotypic abnormality - Chih-Ping Chen; Schu-Rern Chern; Yen-Ni Chen; Shin-Wen Chen; Peih-Shan Wu; Chien-Wen Yang; Chen-Chi Lee; Meng-Shan Lee; Chen-Wen Pan; Wayseen Wang (Elsevier, 2017)
Objective: We present prenatal diagnosis and molecular cytogenetic characterization of concomitant familial small supernumerary marker chromosome 4 [sSMC(4)] derived from 4q11.1-q12 and q13.2, and 5q13.2 microdeletion with no apparent phenotypic abnormality. Materials and methods: A 32-year-old woman underwent amniocentesis at 21 weeks of gestation because of absent nasal bone on fetal ultrasound. Amniocentesis revealed a karyotype of 47,XX,+mar[13]/46,XX[3]. Array comparative genomic hybridization analysis on the cultured amniocytes revealed a 2.752-Mb duplication at 4q11-q12, a 1.949-Mb duplication at 4q13.2, and a 1.65-Mb deletion at 5q13.2. The woman underwent repeat amniocentesis at 24 weeks of gestation for molecular cytogenetic characterization. The phenotypically normal parents and their elder son underwent genetic analysis. Results: At repeat amniocentesis, interphase fluorescence in situ hybridization analysis on uncultured amniocytes revealed 79.25% (84/106) mosaicism for the sSMC(4), and metaphase fluorescence in situ hybridization analysis on cultured amniocytes revealed that all 20 cells examined (100%) had the sSMC(4). Polymorphic DNA marker analysis on uncultured amniocytes excluded uniparental disomy 4. The father had a karyotype of 47,XY,+mar[2]/46,XY[38], and interphase fluorescence in situ hybridization revealed 2.91% (3/103) mosaicism for the sSMC(4) in his peripheral blood. The mother carried the 5q13.2 microdeletion. The elder son had a karyotype of 47,XY,+mar[27]/ 46,XY[13] with duplications of 4q11-q12 and 4q13.2. A 3105 g female baby was delivered at term with no apparent phenotypic abnormality. Conclusion: Prenatal diagnosis of concomitant sSMC and microdeletion should raise a suspicion of familial inheritance.